Enhanced Bioactivity and Anti-microbial Properties of Lactobacillus plantarum Fermented Purple Onion (Allium cepa L.) Extracts Against Selected Poultry Microbes - Phan Vu Hai; Ho Dung; Tran Nguyen Thao; Nguyen Xuan Hoa; Pham Hoang Son Hung (Poultry Science Journal, 2025)
This study aimed to optimize the fermentation process of purple onion extract (POE) using Lactobacillus plantarum 1582 and evaluate the biological properties of the fermented product (FPOE). The L. plantarum 1582 strain, selected for its high survivability in POE, was fermented under optimal conditions of 30% POE concentration for 24 hours, resulting in significant bacterial growth. Post-fermentation analysis revealed an increase in total flavonoid content (P = 0.023) and decreases in phenolic, thiol, and allicin levels by 15.4% (P < 0.05), 11.4% (P < 0.05), and 12.6% (P < 0.05), respectively. Using LC-MS, two new sulfur-containing volatile compounds—2-vinyl-4H-1,3-dithiine and γ-glutamyl-S-2-propenyl-cysteine—were identified in FPOE. These compounds were not present in fresh POE. Antioxidant activities of FPOE, assessed through ABTS and DPPH assays, significantly decreased after fermentation. This study provides essential data on the biochemical changes and novel compound formation during the fermentation of POE with L. plantarum 1582, suggesting its potential for applications in the feed or functional food industries.